Perencanaan Analisis Pengendalian Kualitas Untuk Menurunkan Cacat Thickness Produk Kemasan Sauce Powder Pada Mesin Extruder Dengan Metode Failure Mode and Effect Analysis (FMEA) - Sinaga, Zulkani; Muhazir, Achmad; Dewi, Deby Cika (Jurnal Optimalisasi, 2025)
PT. XYZ Packaging Division is a company engaged in the food sector, especially the packaging sector. In 1 year of sauce powder packaging production, there were defective products produced exceeding the company's permitted limits, and the highest defect value was 4.7%. The highest percentage of defects occurred in the extruder process, this study will focus on the analysis of defective products produced from the extruder process. The high level of defective products in the sauce powder packaging production process occurs in the extruder process, namely thickness variation type defects. To reduce the level of defective products that occurred in this study, failure mode and effect analysis (FMEA) and seven tools were used, this method can analyze and reduce the level of product defects through a product failure model based on calculations of severity, occurrence and detection, then the RPN (risk Priority Number) value will be known, the cause of failure that has the highest RPN, that is the possible cause of high defects produced in the production process. From the results of the study, it is known that the dominant factor that causes the high level of defects in thickness variations is caused by dirty material factors and problematic machine factors in the polymer flow process. The results of problem solving with FMEA and seventools obtained a significant reduction in the level of defects in the extruder process from 3% to 1.4%, the recommended improvement results can reduce the level of defects in the extruder process to below the standard set by the company, which is 2.5%.